Ramadan Effect: Evidence from Borsa Istanbul - TAN, ÖMER FARUK (My University, 2017)
This study analyzes the effect of Ramadan on the market index (Borsa Istanbul-BIST 100) and 23 BISTSectoral Indices in Borsa Istanbul over the period between January 1997 and December 2015. Accordingto the analysis, the average returns of tourism, service, transportation, electricity, and chemical industriesare higher than the market index during the Ramadan period. Moreover, according to regression analysisresults, Ramadan has a statistically positive effect on 5 sectors (BIST Transportation, BIST Non-MaterialMineral Products, BIST Investment Trust, BIST Electricity, and BIST Chemicals). Also, this study dividesthe Ramadan days into 3 periods, where the first period comprises the first 10 days of Ramadan, secondperiod covers the next 10 days, and the final period involves the last 10 days. The first ten days of Ramadan,for the most of indices, has both positive and statistically significant returns.

Bu çalışma Ocak 1997-Aralık 2015 yılları arasında Borsa İstanbul (BIST100) ve 23 Borsa İstanbul sektörel endeksinde Ramazan etkisini analiz etmiştir. Sonuçlara göre, Ramazan döneminde, BIST Turizm, BIST Hizmet, BIST Ulaştırma, BIST Elektrik ve BIST Kimya Petrol Plastik sektörlerinin ortalama getirisi piyasa endeksinden daha fazladır. Ayrıca, regresyon analizi sonuçlarına göre, Ramazan ayı 5 sektör için– BIST Ulaştırma, BIST Taş-Toprak, BIST Menkul Kıymet Yatırım Ortaklığı, BIST Elektrik ve BIST Kimya Petrol Plastik- pozitif ve istatistiki olarak anlamlı çıkmıştır. Bu çalışma ayrıca Ramazan dönemini birinci 10 gün, ikinci 10 gün ve üçüncü 10 gün diye ayırarak incelemiştir. Ramazan’ın birinci 10 günü birçok sektör endeksi için pozitif ve istatistiki olarak anlamlı çıkmıştır.
Ramazan Etkisi: Borsa İstanbul Örneği